Identifying Barriers to the Remix of Translated Open Educational Resources - Amiel, Tel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Remix is touted as one of the most important practices within the field of open educational resources (OER). But remixing is still not mainstream practice in education and the barriers and limitations to remix are not well known. In this article we discuss the design and development of a print and web-based booklet created to introduce the topic of OER to schoolteachers. The guide, the first of its kind available in Portuguese, was created through the remix and translation of existing resources available in English. Choosing design-as-remix raised a series of concerns related to licensing, attribution, context, and technical standards. In this article we review the concerns related to culture and inequity within the OER movement, followed by the design choices and procedures, and finally the implications of these issues for the open educational resources movement.